046 Preparing new registrars for practice in the age of Zoom. Issue 6 (27th May 2022) - Rees, Richard; Russell, Amy Ross; Patel, Faheemah; Lawrence, Joanne; Jones, Matthew; Warner, Tom
Abstract : Introduction: In 2019 the ABN delivered the first Acute Neurology Boot Camp. This addressed an unmet need in post-graduate training. We designed a one-day series of seminars covering common or critical presentations for neurology registrars on-call. In 2020, face-to-face events weren't feasible, and while having to adapt to a new model of working including tele-neurology, virtual radiology meetings, we adapted the boot camp to this model. Methods: We designed an online version of the boot camp over two weeks. Videos were recorded for repeat viewing. All delegates were encouraged to complete surveys on confidence levels, before and after each session, and with reference to the course as a whole. Results: 77 participants provided feedback. 289 logged-in live and YYY have viewed the videos on-demand. This compares to XYZ in the 2019 iteration. 30% of respondents were confident or very confident at being the neurology registrar on-call prior to the course, compared to 88% at the end of the course (p< 0.00001). Participants were very happy with the delivery, content and format of the talks, with "very good" ratings for 60%, 56% and 57% respectively. Conclusion: The Covid-19 pandemic brought tumultuous shifts in practice that were uncharted waters for the entire neurological community. As we all tried to stay afloat, we also provided a necessary life-raft to trainees who were negotiating the challenge of the transition to being a neurology registrar. rnrees@gmail.com|ABN Bursary 48